Slipped capital femoral epiphysis in adults: case report and review of literature - C.C. Macía-Villa; I. Sanchez-Lite; J. Medina-Luezas (PAGEPress Publications, 2016)
Slipped capital femoral epiphysis (SCFE) mainly affects overweight prepubertal children. It is usually idiopathic, but endocrinological diseases are proposed as the main cause. SCFE occurs before the closing of the femoral physis, which generally occurs at 18 years in males and 16 years in females, therefore it is considered a children's disease. However, there have been several reports of adults with SCFE and some familial cases. We present a case of bilateral SCFE in a 47 years old female with possible relationship with inhaled corticosteroids, and for the first time we collect and analyze all published cases in adults.